Proposal for the formation of categories in women's wrestling according to statistics and anthropological characteristics by continent - Barbas, I. (International Journal of Wrestling Science, 2024)
The formation of weight classes in wrestling is done by United World Wrestling (UWW), with the aim of balancing the physical capabilities of the athletes and promoting fair competition. Weight categories are formed taking into account the physical characteristics of female athletes, participation statistics and differences by continent. Based on data on average kilograms per continent and women's participation in wrestling, ten weight classes have been proposed that correspond to different levels of body weight and competition.